Tajdid dan Transformasi Pendidikan Islam Era Industri 4.0 Dalam Hadis Tarbawi - Fauziah Della Iftinah; Salsa Nabila; Dwi Meutia Hasni (ABANNA: Journal Of Contemporary Islamic Education, 2026)
This study examines the concept of tajdīd from the perspective of Hadith Tarbawi and its relevance to the transformation of Islamic education in the era of the Fourth Industrial Revolution. Tajdīd is understood as an effort to renew and revitalize Islamic teachings while maintaining the fundamental principles of Islamic law. In the educational context, tajdīd seeks to revive Islamic educational values based on the Qur'an and Sunnah in order to respond to contemporary developments and societal needs. Although previous studies have discussed educational reform in Islam and the challenges posed by the digital era, studies that specifically integrate the concept of tajdīd from the perspective of Hadith Tarbawi with the transformation of Islamic education in the era of the Fourth Industrial Revolution remain limited. This study employs a library research method with a descriptive-analytical approach to examine hadiths related to educational renewal in Islam. The findings reveal that Islamic education in the era of the Fourth Industrial Revolution faces various challenges, including moral crises, the decline of ethical values, the dominance of digital technology, weak spiritual literacy, and the dichotomy between religious and secular sciences. From the perspective of Hadith Tarbawi, the transformation of Islamic education can be achieved through the renewal of learning methods, the development of an integrative curriculum, the strengthening of spirituality and character education, and the revitalization of teachers' roles as mentors and guardians of knowledge. Therefore, the concept of tajdīd serves as an essential foundation for developing an adaptive, innovative, and humanistic Islamic educational system that remains firmly grounded in Islamic values amid rapid technological advancement.